Clinical characteristics and genetic analysis of A20 haploinsufficiency - Dan Zhang; Gaixiu Su; Zhixuan Zhou; Jianming Lai (BMC, 2021)
Abstract Purpose To evaluate the clinical and genetic characteristics of 3 children with Haploinsufficiency of A20 (HA20). Methods:The clinical and genetic testing data of 3 children with HA20 treated at Capital Institute of Pediatrics (CIP) between August 2016 and October 2019 were retrospectively analysed. Result Patient 1 presented with arthritis and inflammatory bowel disease, patient 2 presented with axial spinal arthritis and lupus-like syndrome, and patient 3 presented with recurrent oral ulcers, gastrointestinal ulcers, and perianal abscesses. Regarding laboratory tests, patients were found to have elevated white blood cell (WBC) count, C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). The CRP and ESR was reported to be high in all the patients. The WBC was reported to be high in patient 1 and 3. Patient 2 was positive for antinuclear antibodies, anti-Sjögren's syndrome antigen A, dsDNA, rheumatoid factor and Coombs test. Genetic testing showed that all three patients had heterozygous mutation in TNFAIP3 gene. As for the treatment, patient 1 was treated with TNFα antagonist, patient 2 was treated with TNF α antagonist and sulfasalazine, and patient 3 was treated with corticosteroids and thalidomide. Patients 1 and 2 were followed for four and 3 months, respectively. There was an improvement in joint and gastrointestinal symptoms; inflammatory indices and rheumatoid factor (RF) were normal, and dsDNA and Coombs test became negative. Patient 3 was treated at another hospital and showed gradual improvement in oral ulcers and perianal abscesses. Conclusion HA20 is a single-gene auto-inflammatory disease caused by mutation in tumour necrosis factor (TNF)-α-induced protein 3 (TNFAIP3) gene. It may present as Behçet-like syndrome and resemble various other autoimmune diseases as well. Corticosteroids and immunosuppressive agents are effective treatments, and cytokine antagonists can be used in refractory cases. Whole-exome genetic testing should be proactively performed for children with early-age onset or Behçet-like syndrome to achieve early diagnosis and accurate treatment.